The Industry of Marrying Europeans - Vũ, Trọng Phụng, 1912-1939 (Book collections on Project MUSE., 2006)
"This work by Vu Trong Phung, written in the 1930s, reports and expands on the author's meetings with North Vietnamese women who had made an "industry" of marrying European men. The Industry of Marrying Europeans is notable for its sharp observations, pointed humor, and unconventional mix of nonfictional and fictional narration, as well as its attention to voice: Vu Trong Phung records the French-Vietnamese pidgin dialect spoken by these couples. This prolific writer died at age twenty-seven, leaving behind one of the most impressive bodies of work in modern Vietnamese literature."--Amazon.com